A Meshless Method to Determine a Source Term in Heat Equation with Radial Basis Functions - Wang, Baiyu; Liao, Anping (Chinese journal of mathematics, 2013)
This paper considers a numerical method based on the radial basis functions for the inverse problem of heat equation; the inverse problem is determining an unknown source term subject to the overdetermination along with the usual initial boundary conditions, and the unknown source term is only time-dependent. The radial basis functions method is a meshless method with high accuracy for the inverse problem. Some numerical experiments using this method are presented and discussed.